Características de la efectividad de esquemas antineoplásicos utilizados en pacientes pediátricos con leucemia linfoblástica aguda adscritos al Hospital Virgen de la Puerta - Trujillo 2016 - Calderón Beltrán, Shaarón Lisseth (2017)
The present report was designed to characterize the effectiveness of the antineoplastic regimens used in pediatric patients with Acute Lymphoblastic Leukemia (ALL) ascribed to Hospital Virgen de la Puerta in 2016. For this, the medical records of pediatric patients with the guidelines of the LAL / SEHOP-PETHEMA 2013 Therapeutic Recommendations. The effectiveness characterization was assessed by the percentage of pediatric patients deceased diagnosed with ALL and, therefore, the causes of these patients' deaths were determined. The percentage of patients who went through the maintenance phase is also represented. There were 24 pediatric patients, 6 of whom died, one of the causes that stands out is the infection that is a potentially deadly complication of chemotherapy in children with ALL, 4 cases were reported out of a total of 6 patients who died. The 61% of patients with ALL who went on to the maintenance stage the high probability of cure is a significant proportion of cancers in pediatric patients